Komposisi dan Kelimpahan Moluska (Gastropoda dan Bivalvia) - Rani Lasari; Arman Harahap (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the composition and abundance of mollusks (Gastropods and Bivalves) in the Aek Pala River, Labuhanbatu Regency. The method used is purposive random sampling. Sampling was carried out using a net source. The results showed that the Gastropod groups found were Pachychilidae, Ampullaridae, Littorinidae, Nassaridae, Thiaridae, Hydrobiidae, Tateidae, Spiraxidae, Vivipararidae and Batillariidae, while the Bivalvia groups were Corbiculidae and Curbulidae. In conclusion, the composition of mollusks found were 10 families of Gastropods and 2 families of Bivalves. Keywords: Bivalves, Gastropods, Abundance, Composition, Molluscs